1994
DOI: 10.1136/adc.70.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to endotoxin core in sudden infant death syndrome.

Abstract: (Arch Dis Child 1994; 70: 95-98)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 11 publications
0
31
1
Order By: Relevance
“…There is both theoretical and experimental evidence in support of the hypothesis that toxins produced by bacteria that commonly colonise the nasopharynx have a pathogenic role in sudden infant death syndrome (SIDS) [1–7]. This idea, which is reviewed elsewhere in this issue, is consistent with the key epidemiological features of SIDS including the age distribution, the winter excess of cases and the association with prone sleeping and passive smoking.…”
Section: Introductionmentioning
confidence: 76%
“…There is both theoretical and experimental evidence in support of the hypothesis that toxins produced by bacteria that commonly colonise the nasopharynx have a pathogenic role in sudden infant death syndrome (SIDS) [1–7]. This idea, which is reviewed elsewhere in this issue, is consistent with the key epidemiological features of SIDS including the age distribution, the winter excess of cases and the association with prone sleeping and passive smoking.…”
Section: Introductionmentioning
confidence: 76%
“…16,18,20 In a large number of SIDS victims, postmortem microbiologic assessment of the upper respiratory tract revealed numerous and varied bacterial species, 4 particularly gram-negative Escherichia coli isolate, which contain endotoxin in the cell wall, being potent stimulator of proinflammatory cytokines IL-1, IL-6, TNF-␣, and interferon-␥. 25 Many of the gram-positive bacteria found in SIDS victims were toxicogenic and produced superantigens, 23 eg, Staphylococcus aureus, which could induce abnormalities in the body characteristic for septic shock, even without symptoms of endotoxemia. 25 Many of the gram-positive bacteria found in SIDS victims were toxicogenic and produced superantigens, 23 eg, Staphylococcus aureus, which could induce abnormalities in the body characteristic for septic shock, even without symptoms of endotoxemia.…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%
“…It has been suggested that toxins associated with bacteria that infants commonly encounter during the first few months of life might be adsorbed through the respiratory tract and precipitate the series of events that lead to SIDS [1–5]. There is evidence for involvement of both endotoxins of Gram‐negative bacteria [7] and powerful exotoxins produced by Staphylococcus aureus [8–10]. Epidemiological studies have also implicated Bordetella pertussis [11,12].…”
Section: Introductionmentioning
confidence: 99%